Chloroquine-induced DNA damage synergizes with DNA repair inhibitors causing cancer cell death - Iglesias-Corral, Diego; García-Valles, Paula; Arroyo-Garrapucho, Nuria; Bueno-Martínez, Elena; Ruiz-Robles, Juan Manuel; Ovejero-Sánchez, María; González-Sarmiento, Rogelio; Herrero, Ana Belén (Frontiers in Oncology, 2024)
Background: Cancer is a global health problem accounting for nearly one in six deaths worldwide. Conventional treatments together with new therapies have increased survival to this devastating disease. However, the persistent challenges of treatment resistance and the limited therapeutic arsenal available for specific cancer types still make research in new therapeutic strategies an urgent need.: Chloroquine was tested in combination with different drugs (Panobinostat, KU-57788 and NU-7026) in 8 human-derived cancer cells lines (colorectal: HCT116 and HT29; breast: MDA-MB-231 and HCC1937; glioblastoma: A-172 and LN-18; head and neck: CAL-33 and 32816). Drug´s effect on proliferation was tested by MTT assays and cell death was assessed by Anexin V-PI apoptosis assays. The presence of DNA double-strand breaks was analyzed by phospho-H2AX fluorescent Código de campo cambiado Código de campo cambiado staining. To measure homologous recombination efficiency the HR-GFP reporter was used, which allows flow cytometry-based detection of HR stimulated by I-SceI endonuclease-induced DSBs.The combination of chloroquine with any of the drugs employed displayed potent synergistic effects on apoptosis induction, with particularly pronounced efficacy observed in glioblastoma and head and neck cancer cell lines. We found that chloroquine produced DNA double strand breaks that depended on reactive oxygen species formation, whereas Panobinostat inhibited DNA double-strand breaks repair by homologous recombination. Cell death caused by chloroquine/Panobinostat combination were significantly reduced by N-Acetylcysteine, a reactive oxygen species scavenger, underscoring the pivotal role of DSB generation in CQ/LBH-induced lethality. Based on these data, we also explored the combination of CQ with KU-57788 and NU-7026, two inhibitors of the other main DSB repair pathway, nonhomologous end joining (NHEJ), and again synergistic effects on apoptosis induction were observed.Our data provide a rationale for the clinical investigation of CQ in combination with DSB inhibitors for the treatment of different solid tumors.